Pengaruh kepemimpinan kepala sekolah terhadap kinerja guru SD Di Kecamatan Brati Kabupaten Grobogan - Kamidah, Nur; Abdullah, Ghufron; Ariyanto, Lilik (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
Teacher performance is a crucial indicator in improving the quality of primary education. The 2025 Education Report data show that 34.48% of public elementary schools in Brati District fall into the low category in the learning quality dimension. Supervision reports also indicate that 53% of teachers have incomplete learning administration and 65% have not implemented varied teaching methods. These conditions are presumably related to suboptimal principal leadership, particularly in supervision, innovation, and motivation functions. This study aims to analyze the effect of principal leadership on teacher performance in public elementary schools in Brati District, Grobogan Regency. This research employed a quantitative approach using a survey method. The population consisted of elementary school teachers in Brati District, with samples selected through proportional random sampling. Data were collected using validated and reliable questionnaires and analyzed using simple linear regression. The results indicate that principal leadership has a positive and significant effect on teacher performance. The more effective the principal’s leadership, the higher the teacher performance. This study emphasizes the strategic role of principals as supervisors, motivators, and innovators in improving teacher performance. Abstrak Kinerja guru merupakan indikator penting dalam peningkatan mutu pendidikan dasar. Data Rapor Pendidikan Tahun 2025 menunjukkan bahwa 34,48% Sekolah Dasar di Kecamatan Brati berada pada kategori kurang dalam dimensi kualitas pembelajaran. Selain itu, hasil supervisi menunjukkan 53% guru belum melengkapi administrasi pembelajaran dan 65% belum menggunakan metode pembelajaran yang variatif. Kondisi tersebut diduga berkaitan dengan kepemimpinan kepala sekolah yang belum optimal, terutama dalam fungsi supervisi, inovasi, dan pemberian motivasi. Penelitian ini bertujuan untuk menganalisis pengaruh kepemimpinan kepala sekolah terhadap kinerja guru Sekolah Dasar di Kecamatan Brati Kabupaten Grobogan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Populasi penelitian adalah guru Sekolah Dasar di Kecamatan Brati, dengan teknik pengambilan sampel menggunakan proportional random sampling. Pengumpulan data dilakukan melalui kuesioner yang telah diuji validitas dan reliabilitasnya. Data dianalisis menggunakan regresi linear sederhana. Hasil penelitian menunjukkan bahwa kepemimpinan kepala sekolah berpengaruh positif dan signifikan terhadap kinerja guru. Semakin efektif kepemimpinan kepala sekolah, semakin tinggi pula kinerja guru. Penelitian ini menegaskan pentingnya peran kepala sekolah sebagai supervisor, motivator, dan inovator dalam meningkatkan kinerja guru di sekolah dasar.